2021
DOI: 10.3390/genes12060826
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Asymmetries in the SARS-CoV-2 Genome May Lead to Increased Hydrophobicity of Virus Proteins

Abstract: The genomic diversity of SARS-CoV-2 has been a focus during the ongoing COVID-19 pandemic. Here, we analyzed the distribution and character of emerging mutations in a data set comprising more than 95,000 virus genomes covering eight major SARS-CoV-2 lineages in the GISAID database, including genotypes arising during COVID-19 therapy. Globally, the C>U transitions and G>U transversions were the most represented mutations, accounting for the majority of single-nucleotide variations. Mutational spectra were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The near leveling of the hydrophobic peak near 227 with the receptor binding peak near 380 suggests that the two peaks could bind together to aerosol surfaces. It had been noted previously that CoV-2 mutations favored hydrophobic residues [29] . Thus, we hypothesize that Delta may have become more transmissible by improving its binding ability to ACE2 while the others have preserved their ability to bind but possibly improved function elsewhere, such as being more stable outside of the host or replicating at a faster rate within the host.…”
Section: Resultsmentioning
confidence: 80%
“…The near leveling of the hydrophobic peak near 227 with the receptor binding peak near 380 suggests that the two peaks could bind together to aerosol surfaces. It had been noted previously that CoV-2 mutations favored hydrophobic residues [29] . Thus, we hypothesize that Delta may have become more transmissible by improving its binding ability to ACE2 while the others have preserved their ability to bind but possibly improved function elsewhere, such as being more stable outside of the host or replicating at a faster rate within the host.…”
Section: Resultsmentioning
confidence: 80%
“…All these results support a stronger mutational bias in SCoV2rC and PangSar genomes characterised by higher rates for C=>U and G=>A transitions than for the reverse mutations (U=>C and A=>G, respectively). Previous studies examining the nucleotide composition in SARS-CoV-2 genomes have all concluded to an overrepresentation of C=>U transitions (Rice et al 2020;Matyášek et al 2021). Several mechanisms have been proposed to account for the cytosine deficiency in the genome of sarbecoviruses, such as cytosine deamination resulting from the action of the host APOBEC system (Milewska et al 2018), methylation of CpG dinucleotides (Xia 2020), or the limited availability of cytidine triphosphate (CTP), which is used not only for the viral RNA genome synthesis but also for the synthesis of the virus envelope, as well as translation and glycosylation of viral proteins (Ou et al 2021).…”
Section: Evidence For Seven Groups Of Snc Among Sarbecovirus Genomesmentioning
confidence: 99%
“…Since the replication process is dependent of the host cell, a viral host-shift to a new mammalian species (i.e., from the reservoir to a secondary host or from an intermediate host to a terminal host) may result in important changes in the mutational patterns driving the evolution of viral genomes. For instance, it has been shown that most SARS-CoV-2 mutations in human populations are represented by C=>U transitions (Rice et al 2020;Matyášek et al 2021). With time, such a mutational bias can affect the nucleotide content of viral genomes.…”
Section: Introductionmentioning
confidence: 99%
“…In the later part of the pandemic (September 2020 onwards) when most of the spike genes followed SPMHR pattern (i.e., higher hydrophobic) mostly belongs to G clade and its derivatives (Figure S1 ). 29 …”
Section: Resultsmentioning
confidence: 99%